Implementation Fiduciary Registration According to Finance Ministry, Police, and Financial Services Authority (OJK) - Suwinto Johan (Bina Nusantara University, 2021)
The research aimed to research fiduciary guarantees registration from a legal perspective, especially the executive or administrative regulations. The research examined the existing regulations and laws by analysing primary and secondary data using normative juridical methods. There were three legal material inventory, namely primary legal materials, secondary legal materials, and tertiary legal materials. The research concludes that the fiduciary registration obligations stipulated in the Regulation of Minister of Finance (PMK) Number 130/PMK.010/2012 are not in synchronic with the Financial Services Authority Regulation (POJK) Number 29/POJK.05/2014, which was replaced by the Financial Services Authority Regulation Number 35/POJK.05/2018. Revocation of Regulation of Minister of Finance Number 130/PMK.010/ 2012 by Regulation of the Minister of Finance Number 23/PMK.010/2017 is not accompanied by amendments to the Regulation of the Republic of Indonesia National Police Number 8 of 2011. The loan agreement remains valid if it fulfills the principles of the agreement. It is suggested that relevant institutions, particularly the Financial Services Authority (OJK) as the financial industry supervisor, take initiatives to synchronize all regulations for the implementation of fiduciary registration.